2021
DOI: 10.1038/s41598-021-83622-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data of fulvestrant as first-line treatment of postmenopausal women with estrogen receptor-positive metastatic breast cancer

Abstract: Goals of endocrine therapy for advanced breast cancer (ABC) include prolonging survival rates, maintaining the quality of life, and delaying the initiation of chemotherapy. We evaluated the effectiveness of fulvestrant as first-line in patients with estrogen receptor (ER)-positive ABC with relapse during or after adjuvant anti-estrogenic therapy in real-world settings. Retrospective, observational study involving 171 postmenopausal women with ER-positive ABC who received fulvestrant as first-line between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Fulvestrant has been used as a first-line treatment to meet the targets of endocrine therapy, including extending survival rates, maintaining the quality of life, and delaying the initiation of chemotherapy in patients with advanced ER-positive breast cancer [ 58 ]. Despite the established efficiency of hormonal therapy, one in three patients developed resistance in one study [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fulvestrant has been used as a first-line treatment to meet the targets of endocrine therapy, including extending survival rates, maintaining the quality of life, and delaying the initiation of chemotherapy in patients with advanced ER-positive breast cancer [ 58 ]. Despite the established efficiency of hormonal therapy, one in three patients developed resistance in one study [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…ER signaling plays a crucial role in BC proliferation, invasion, and angiogenesis. Mechanisms, through which the endocrine therapy works (refer to Table 1 ), can be categorized into (1) SERMs, (2) aromatase inhibitors (AIs), (3) CDK4/6 inhibitors, and (4) SERDs ( Figure 4D ) ( 148 , 149 ). SERMs function by sitting in the ER of breast tissues, blocking the estrogen from interacting with the ER, and hence the cells can no longer grow and multiply ( 150 ).…”
Section: Mechanism Of Bcsc-mediated Drug Resistance To Cancer Therapymentioning
confidence: 99%
“…Fulvestrant is a selective estrogen receptor degrader (SERD) administered in both first and subsequent lines of treatment in ER-α+ metastatic BC patients ( 149 , 168 ). Fulvestrant competitively inhibits estrogen to occupy the ER, eventually promotes degradation of the receptor, and thus interferes with estrogen signaling in breast tumor tissues ( 169 ).…”
Section: Mechanism Of Bcsc-mediated Drug Resistance To Cancer Therapymentioning
confidence: 99%
“…Fulvestrant inevitably causes drug-related adverse reactions while treating breast cancer. A review of medical records of 171 patients with locally advanced or metastatic HR+/HER2- breast cancer who received fulvestrant treatment showed that 66.9% of patients experienced drug-related adverse reactions, with severe adverse reactions accounting for 8.6% of cases 8 . In recent years, there has been growing concern about adverse reactions in endocrine therapy for breast cancer.…”
Section: Introductionmentioning
confidence: 99%